Evolution of Bacterial Cellulose in Cosmetic Applications: An Updated Systematic Review - Thais Jardim Oliveira; Talita Cristina Mena Segato; Gabriel Pereira Machado; Denise Grotto; Angela Faustino Jozala (Molecules, 2022)
In recent decades, there has been an increase in environmental problems caused by cosmetic products derived from toxic substances. Based on this issue, researchers and developers of new beauty cosmetics are looking for new natural alternatives that work well for the consumer and have biodegradable characteristics. This systematic review highlights the major publications of bacterial cellulose used strictly for cosmetics in the last 10 years. Bacterial cellulose is a natural product with great cosmetic properties and low cost that has shown excellent results. This study aimed at collecting rigorous information on bacterial cellulose in the cosmetic field in the last decade to produce a systematized review. A comprehensive search was conducted with selected descriptors involving the topic of “bacterial cellulose”, “cosmetics”, “clean beauty”, and “skin mask”. Seventy studies were found, which went through exclusion criteria that selected only those related to the topic that was searched. In the 12 remaining studies that met the criteria, bacterial cellulose showed conditions for use as a mask-forming product for facial care. The increase in the number of publications concerning bacterial cellulose in cosmetics in the last ten years is a strong indicator that this is a growing area for both research and the industry.